GENERAL RULES ON RESPONSIBILITY - Knežević, Mirjana (Law - Theory and Practice, 2010)
Having in mind the rule of subsidiar application of civil law when there are no specific legal provisions for certain types of transportation, having in mind that regarding the amount of reimbursement transporter is responsible according to the same programs like other persons, we have exposed in thispaper basic regulations of the civil legal responsibilirv forthe damages. The problem of the responsibilirv of the transporter becomes in time one of the most interpreted legal questions, because the users of transportation want to know evervthing about legal consequences of traffic accidents, rights that would have members of their families in case of their death or their own reimbursement in case that they survive accident. When we speak about responsibility of the transporter for death and injury of the passengers, we speak about rights of the passengers or their relatives for the financial reimbursement or non financial reimbursement. Loss of life and damaged health can not be financialv compensated, but the responsibilitv of the transporter for the death and body injuries of the passengers gives legal protection of the passengers and shovvs it’s legal meaning. Extraordinary efforts are conducted in the area of unification of rules regarding responsibility of the transporter, but unification of the rules on responsibilities of the transporter for the damages on goods was much earlier and was more succesfully performed then the responsibility of the transporter for death and body injuries of the passengers.